2018
DOI: 10.1038/am.2017.225
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum disulfide/graphene oxide nanocomposites show favorable lung targeting and enhanced drug loading/tumor-killing efficacy with improved biocompatibility

Abstract: Selective targeting plus optimal biocompatibility is still a big challenge in nanomedicine. Although many nanomaterials including graphene oxide (GO) and molybdenum disulfide (MoS 2 ) have been tested for this purpose, these materials possess both favorable features and drawbacks, which hampers their further development. Herein, we prepared MoS 2 /GO nanocomposites that manifested excellent dispersity in aqueous solutions and revealed acceptable biocompatibility in vitro and in vivo. Importantly, MoS 2 /GO dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 80 publications
1
37
0
1
Order By: Relevance
“…Moreover, a hydrophobic effect contributed to the interaction between GO and DOX. 33 In the present study, we reported a novel nanohybrid formed by CS-prGO and DOX and characterized it using cyclic voltammetry, FE-SEM, and FTIR and UV-Vis spectroscopy methods. Furthermore, the loading and release of DOX were investigated by UV-Vis spectroscopy.…”
Section: Introductionmentioning
confidence: 94%
“…Moreover, a hydrophobic effect contributed to the interaction between GO and DOX. 33 In the present study, we reported a novel nanohybrid formed by CS-prGO and DOX and characterized it using cyclic voltammetry, FE-SEM, and FTIR and UV-Vis spectroscopy methods. Furthermore, the loading and release of DOX were investigated by UV-Vis spectroscopy.…”
Section: Introductionmentioning
confidence: 94%
“…1,2 Therefore, GO may have promising applications in drug delivery. 3 For example, Xu's group reported a multifunctional theranostic nanoplatform based on graphene oxide (GO) and MnWO 4 . GO, used as the carrier, possessed a high loading capacity for the anticancer drug doxorubicin hydrochloride (DOX) due to noncovalent forces and the drug release could be triggered by a lower pH value.…”
Section: Introductionmentioning
confidence: 99%
“…GO contains abundant reactive surface functional groups, and likely undergo significant alterations to the 3S factors (size, shape and surface chemistry) once encountering ions and various biomolecules in the biological media 7 - 8 . Thus, after being administrated in vivo , transformation in biological media may greatly alter their predesigned properties, leading to loss of functional groups, oxidation and reduction of the materials, and subsequently either enhances or hinders their intended efficacies in biomedical applications 7 , 9 - 10 .…”
Section: Introductionmentioning
confidence: 99%
“…administration 20 . In a recent study, we found that MoS 2 /GO nanocomposites manifested selective lung targeting owing to GO's lung-targeting property, resulting in enhanced tumor killing efficacy 8 . The tendency of GO materials in targeting lung warrants a thorough understanding of their potential bio-transformation in the lung and the consequences, which have not been studied.…”
Section: Introductionmentioning
confidence: 99%